2023
DOI: 10.3390/rs15020520
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of Regional Groundwater Storage Changes Based on the Fusion of GNSS and GRACE Data: A Case Study of Shaanxi–Gansu–Ningxia

Abstract: This paper aims to address the limitations of the distribution number and uniformity of Continuously Operating Reference Stations (CORS) and their impact on the reliability of inverting regional groundwater storage (GWS) based on Green’s function method and using global navigation satellite system (GNSS) data. A fusion method on the inversion of regional GWS changes from GNSS and the Gravity Recovery and Climate Experiment (GRACE) was proposed in this paper. Taking the Shaanxi–Gansu–Ningxia (SGN) region as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The could be obtained from GRACE data. Because the GLDAS model is widely used to estimate the SnWS and SWS 4 6 . Therefore, the GLDAS with 2.1 version hydrological model of the same period can be adopted to obtain , , .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The could be obtained from GRACE data. Because the GLDAS model is widely used to estimate the SnWS and SWS 4 6 . Therefore, the GLDAS with 2.1 version hydrological model of the same period can be adopted to obtain , , .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, accurately predicting the GWS change can provide an important reference for water resources planning and management. However, the instability and mutability for the time series of GWS changes, as well as the small-sample characteristics of GRACE data, which can bring some difficulties to accurately prediction 6 . The prediction of time series is one of the leading research topics in artificial intelligence 7 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the latest version of the WaterGAP 2.2d model exhibits reasonable performance in simulating key variables such as TWS and human water abstraction (Müller et al [51] ). Therefore, it is used for studying water storage and human water usage (An et al [52] ; Li et al [53] ). We selected data on potential water withdrawals and potential consumptive water use for four sectors: irrigation, industrial, domestic, and livestock, spanning from 2003 to 2016.…”
Section: Hydrological Modelmentioning
confidence: 99%
“…Since GRACE and GNSS-observed surface vertical deformation are independent of each other, the results of GRACE calculations can be validated by comparison [17]. Li et al [18] combined GNSS and GRACE data to estimate changes in groundwater storage in the Shaanxi-Gansu-Ningxia region.…”
Section: Introductionmentioning
confidence: 99%